PENGARUH AKTIFITAS KJA PADA KEBIASAAN MAKAN IKAN KAPIEK (Puntius schawanefeldi) DAN EKONOMI NELAYAN TRADISIONAL PADA WADUK KOTO PANJANG PROPINSI RIAU - Leis Utami Manurung; Sukendi Sukendi; Windarti Windarti; Eni Sumiarsih (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
The presence of fish cage culture activities may affects the environmentalcondition as the remain of fish feed pellets may enter the surrounding water and itmay serve as food resources for wild fish species such as Puntius schawanefeldi .To understand the impact of fish floating cage activities on feeding habit of P.schawanefeldi and economical condition of traditional fishermen in the KotoPanjang Dam, a study has been conducted on April to June 2013. Fish sampleswere collected from 5 stations, Stations 1, 2 and 3 were in the dam, around thecage, while station 4 and 5 were in the area that has no cage. Data of 24 hoursfish feeding habit were obtained by capturing fish for a 3 days period (once/ 3hours, at different time). Stomach content was then removed, identified andanalyzed using a volumetric method. Results shown that the stomach content offish living around the cage and the fish living far from the cage are different.Stomach content of the fish from the 1 st , 2 nd and 3 rd stations was dominated byfish feed pellet remains (>90%), while that of the fish living in the area with nocage was dominated by debris (>90%). These facts indicate P. schawanefeldi is anopportunist fish, its feeding habit is changing. Fish living around the cage preferto feed on commercial fish feed pellet remains. The presence of P. schawanefeldiaround the cage, however, increase the income of traditional fishermen as theyable to caught around 50 – 80 kg of fish/ week, compare to 10 – 20 kg fish/ weekin the 4 th and 5 th stations. Data obtained indicate that the presence of fish cageaffect the feeding habit of P. schawanefeldi and positively affect the income of thetraditional fishermen.Keywords: Puntius schawanefeldi, feeding habit, fish floating cage, KotoPanjang Dam